Power Production from Produced Waters via Reverse Electrodialysis: A Preliminary Assessment - Alessandro Cosenza; Giovanni Campisi; Francesco Giacalone; Serena Randazzo; Andrea Cipollina; Alessandro Tamburini; Giorgio Micale (Energies, 2022)
Wastewaters generated by crude oil extraction processes, called “produced waters” (PWs), are complex solutions that contain organic compounds, mainly hydrocarbons, and often exhibit high salinity. The large amounts of PWs represent a global issue because of their environmental impact. An approach widely used in the oil industry is the reinjection of this wastewater into the extraction wells after a suitable treatment. The high salt concentration of such solutions may be used in salinity gradient technologies to produce green electricity. Among these technologies, reverse electrodialysis (RED) is one of the most promising. In this work, the application of RED for energy generation from two different real oil industry brines was investigated. An experimental campaign was performed by testing 10 × 10 cm2 units in long-run continuous operations, monitoring the performance for more than 25 days. Fouling phenomena, occurring during the continuous operation, decrease the unit performance and several anti-fouling strategies were adopted to tackle this issue. As a result, a positive net power density for up to 18 days of continuous operation was obtained. A maximum power density of about 2.5 W/m2 was observed, demonstrating how the RED technology could be an important strategy to harvest energy from an industrial waste.